2016
DOI: 10.15232/pas.2016-01507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing soybean hulls in finishing diets with wet or modified distillers grains plus solubles on performance and carcass characteristics of beef steers

Abstract: Two experiments evaluated feeding soybean hulls (SBH) in finishing diets that contain distillers grains plus solubles on performance and carcass characteristics. Dietary concentrations of SBH were 0, 12.5, 25, and 37.5% of diet DM. In Exp. 1, 167 crossbred yearling steers (395 ± 22 kg of BW) were fed for 117 d in a randomized block design in which pelleted SBH replaced dry-rolled corn. All diets contained 25% modified distillers grains plus solubles, 15% corn silage, and 5% liquid supplement. As SBH concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
2
7
1
1
Order By: Relevance
“…These results are in line with those described by Freitas et al (2013), who evaluated the production performance of steers fed GC, SH, or wheat bran as carbohydrate sources in 60% concentrate diets and found no significant effects on HCY, which averaged 57.63%. Our results disagree, however, with those published by Bittner et al (2016), who found that HCW declined linearly as they increased the amount of SH in the diet of feedlot steers (389.63, 383.73, 380.56, and 365.59 kg for the levels of 0.0, 12.5, 25.0, and 37.5% of rolled corn replaced with SH). In their experiment, the carcass of the steers that received diets with the maximum SH level was 23.04 kg lighter than that of animals that did not consume SH.…”
Section: Table 4 Means and Standard Errors Of Initial Weight (Iw) Avcontrasting
confidence: 99%
See 3 more Smart Citations
“…These results are in line with those described by Freitas et al (2013), who evaluated the production performance of steers fed GC, SH, or wheat bran as carbohydrate sources in 60% concentrate diets and found no significant effects on HCY, which averaged 57.63%. Our results disagree, however, with those published by Bittner et al (2016), who found that HCW declined linearly as they increased the amount of SH in the diet of feedlot steers (389.63, 383.73, 380.56, and 365.59 kg for the levels of 0.0, 12.5, 25.0, and 37.5% of rolled corn replaced with SH). In their experiment, the carcass of the steers that received diets with the maximum SH level was 23.04 kg lighter than that of animals that did not consume SH.…”
Section: Table 4 Means and Standard Errors Of Initial Weight (Iw) Avcontrasting
confidence: 99%
“…In Brazil, SFT values between 3-10 mm are desirable, considering that a minimum thickness of 3 mm is required for proper carcass chilling, without meat darkening or excessive muscle fibre shortening, which considerably compromise meat tenderness. The present results for SFT corroborate those presented by Bittner et al (2016), who found that the level of substitution of rolled corn by SH in the finishing of feedlot steers had no effect on SFT measured at the 12th rib. Those authors obtained an average SFT of 3.09 mm.…”
Section: Table 4 Means and Standard Errors Of Initial Weight (Iw) Avsupporting
confidence: 92%
See 2 more Smart Citations
“…A casca de soja (Glycine max) é um subproduto advindo da indústria de óleos comestíveis, obtido após a quebra do grão para extração do óleo, sendo composto, em maior quantidade, pelo pericarpo do grão, a capa protetora da semente (IPHARRAGUERRE;CLARK, 2003). Este subproduto possui um alto teor de fibra, não se enquadrando na alimentação humana, mas com uma composição com potencial de utilização na nutrição animal (BITTNER et al, 2016;ELGHANDOUR et al, 2017 Alguns estudos têm demonstrando o potencial desse subproduto na alimentação animal (ADAMAFIO et al, 2012;PAN et al, 2019), e devido ao seu alto conteúdo fibroso, a casca de amendoim pode ser fonte de volumoso de baixa qualidade para ruminantes e ser fonte de fibra em dietas de alta carga energética a fim de garantir a saúde do rúmen.…”
Section: Casca De Sojaunclassified